Geodetic strain of Greece in the interval 1892-1992 - Davies, R; England, P; Parsons, B; Billiris, H; Paradissis, D; Veis, G (1997)
A first-order triangulation of Greece was carried out in the 1890s. Reoccupation, using Global Positioning System receivers, of 46 of the 93 original markers yielded estimates of the deformation of the region over the intervening interval. Broad regions have similar geodetic strain over the 100-year time span. Strain north of the Gulf of Korinthos is predominantly north-south extension, though with a significant east-west component. The central Peloponnisos is relatively stable, whereas the gulfs of the southern Peloponnisos are all characterized by uniaxial east-west extension. The seismic expression of strain for the entire region, calculated from the seismic moment tensors of earthquakes of MS ≥ 5.8 during the past 100 years, accounts for only 20-50% of the geodetically determined strain. At a scale of 50-100 km, the fraction of the strain that is expressed seismically varies much more than this range. In particular, whereas seismic strain in the eastern Gulf of Korinthos over the past 100 years is commensurate with the geodetic strain, there is rapid extension across the western Gulf of Korinthos (∼0.3 μstrain yr-1), with negligible seismic strain for the 100 year period prior to 1992. The Egion earthquake of June 1995 in the western Gulf of Korinthos released only a small proportion (≤20%) of the elastic strain that had accumulated in that region. The observed distribution of displacements can be explained by the relative rotation of two plates with a broad accommodation zone between them, but it is equally consistent with the deformation that would be expected of a sheet of fluid moving toward a low-pressure boundary at the Hellenic Trench. A simple calculation implies that if the region does behave as a fluid, then its effective viscosity is ∼1022-1023 Pa s. Such viscosities are consistent with the deformation of a lithosphere obeying a rheological law similar to that obtained for olivine in the laboratory.